Proposta de Uma Análise das Forças, Oportunidades, Fraquezas e Ameaças (Matriz Fofa) Para o Desenvolvimento de Microrredes Rurais Hibridas - Frigo, Murilo Miceno; de Lima Caneppele, Fernando; Zullo Godinho, Emmanuel; Fernando Soares Zuin, Luís (Latin American Journal of Energy Research, 2023)
Providing modern energy services in rural areas poses a significant challenge in many countries worldwide. This challenge is further intensified in developing or underdeveloped nations. The geographical and environmental characteristics of these areas further complicate the delivery of these services. In countries with continental dimensions like Brazil, expanding infrastructure is even more costly. However, these geographical factors can be turned into a competitive advantage when one considers the abundance of distributed natural resources. A literature review reveals the potential for rural electrification through hybrid networks, meaning networks powered by more than one primary source. The majority of the studies primarily focus on methods and the application of these methods for optimizing such networks. However, there were limited discussions on regulations and governmental actions concerning microgrids in the selected studies. A SWOT (Strengths, Opportunities, Weaknesses, and Threats) analysis was proposed based on the available literature. In conclusion, if strategically implemented, hybrid microgrids can emerge as a leading solution for the low-carbon energy transition. They can harness distributed energy resources, organic waste that would otherwise be discarded, and cogeneration, all while fostering regional development and job creation. Yet, several challenges persist, such as the need for more robust regulatory frameworks and the advancement of technologies to optimize and intelligently manage these microgrids, epitomizing the concept of "smart grids".